Digital Islamic Education Management: Elementary School Principals' Strategies in Technology-Based Learning and Administration Transformation - Hamdanah, Hamdanah (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study comprehensively examined digital transformation leadership in Madrasah Ibtidaiyah, revealing that successful technology integration depends fundamentally on principals' capacity to navigate complex tensions between modernization and Islamic identity preservation. The research identified five core leadership strategies: visionary technology leadership with clear roadmaps, systematic capacity building through multi-modal professional development, integration of Islamic values in digital content, contextualized blended learning models, and strategic parental engagement. These strategies collectively constitute what we term "Digital-Islamic Leadership"—a synthesis of digital competencies with Islamic educational principles. The four-pillar digital administration model encompassing student information systems, human resource management, financial systems, and communication platforms demonstrated significant efficiency gains while enabling data-driven decision-making and enhanced stakeholder accountability. Importantly, administrative digitalization freed principals to focus on instructional leadership rather than bureaucratic routines, directly contributing to educational quality improvement. Principals successfully navigated four major challenge domains through innovative contextualized solutions: infrastructure limitations addressed via offline-first systems and resource sharing; human capacity gaps overcome through personalized approaches and champion teacher programs; financial constraints managed through creative financing and open-source adoption; and value preservation achieved through Islamic content curation and balanced technology-spiritual integration. The distinction between institutions creating sustainable digital ecosystems versus those pursuing fragmented implementation highlighted that success requires systemic change encompassing vision, structure, culture, and resources—not merely technology procurement. For policy and practice, findings emphasize that digital transformation investments must prioritize leadership development, change management support, and ecosystem building alongside infrastructure provision. Future research should pursue longitudinal studies tracking sustainability, quantitative outcome evaluations measuring learning impacts, and student-centered investigations exploring digital learning experiences. Ultimately, this research demonstrates that thoughtful, contextually-grounded leadership can leverage technology to enhance Islamic education quality while strengthening rather than compromising religious identity and values.